Ruang Budaya Pada Proses Daur Hidup (Kelahiran) Di Dusun Wedoro Gresik - Yuanita, Mike; Antariksa, Antariksa; Wulandari, Lisa Dwi (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2015)
One village in Gresik which still holds cultural ritual is Hamlet Wedoro . Activity life cycle (birth) gradually implemented , from the prenatal to postpartum . Every ritual activity has a space that forms a cultural space . The method used is qualitative descriptive . Analysis using supperimpose map above room space formed , of each ritual activities . Cultural space which is formed not only because of space , the execution time also affects the formation of cultural space . At the birth of the cultural space generated by the micro in residentialKeywords: Cultural space , Birth , Wedoro